79=5x+3(x-3)

Simple and best practice solution for 79=5x+3(x-3) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 79=5x+3(x-3) equation:


Simplifying
79 = 5x + 3(x + -3)

Reorder the terms:
79 = 5x + 3(-3 + x)
79 = 5x + (-3 * 3 + x * 3)
79 = 5x + (-9 + 3x)

Reorder the terms:
79 = -9 + 5x + 3x

Combine like terms: 5x + 3x = 8x
79 = -9 + 8x

Solving
79 = -9 + 8x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-8x' to each side of the equation.
79 + -8x = -9 + 8x + -8x

Combine like terms: 8x + -8x = 0
79 + -8x = -9 + 0
79 + -8x = -9

Add '-79' to each side of the equation.
79 + -79 + -8x = -9 + -79

Combine like terms: 79 + -79 = 0
0 + -8x = -9 + -79
-8x = -9 + -79

Combine like terms: -9 + -79 = -88
-8x = -88

Divide each side by '-8'.
x = 11

Simplifying
x = 11

See similar equations:

| X-17=4x+1 | | 6e+2=2e+5 | | z^3-3z^2+(1+3i)z-6i+2=0 | | 2x-5=3x+18-5 | | 2x-2=8x | | x^2=5+2x | | 6x+1+7x-9=180 | | -3y=-6-x | | Y=5x^2+10x+3 | | -9x=20+4y | | (x+3)*(x-1)-(x-3)*(x+2)=15 | | 3m+2n=p | | 2(q+3)=16 | | 3x+8+2y=1 | | 0=40-2x-10y | | 5(y-1)=2y+7 | | 7*(2x+5)=4x-9-x | | 2(-y-1)-y=-5 | | -6k-13+13=83+13 | | 7*2x+5=4x-9-x | | 90+x+46+x+56=180 | | m+(-6)=2 | | 3+5x=0 | | 4x+9+3x+19+75=180 | | 5m-20=3m | | D=100-6P | | 3(3y+4)+y=4 | | -8-2f=8-6f | | x^2+110x+2000=0 | | -6q=q-7q | | (x+2)+(2x-3)=180 | | 5r=1+5r |

Equations solver categories